(NsTIHOTWORENIQ I PO\MY(B: [1843-1860] / s (N~ASTX (B1s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1965)
(Nw PERWYJ TOM NASTOQ]EGO sOBRANIQ SO^INENIJ n(B. (Na(B. (NnEKRASOWA WO[LI STIHOTWORENIQ I PO\MY(B, (NSOZDANNYE IM W (B1843-1860 (NGG(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\MYs